Given the inequality: (x−3)(x+5)>0 To solve this inequality, we must first solve the corresponding equation: (x−3)(x+5)=0 Solve: Expand the expression in the equation (x−3)(x+5)=0 We get the quadratic equation x2+2x−15=0 This equation is of the form
a*x^2 + b*x + c = 0
A quadratic equation can be solved using the discriminant. The roots of the quadratic equation: x1=2aD−b x2=2a−D−b where D = b^2 - 4*a*c - it is the discriminant. Because a=1 b=2 c=−15 , then
D = b^2 - 4 * a * c =
(2)^2 - 4 * (1) * (-15) = 64
Because D > 0, then the equation has two roots.
x1 = (-b + sqrt(D)) / (2*a)
x2 = (-b - sqrt(D)) / (2*a)
or x1=3 x2=−5 x1=3 x2=−5 x1=3 x2=−5 This roots x2=−5 x1=3 is the points with change the sign of the inequality expression. First define with the sign to the leftmost point: x0<x2 For example, let's take the point x0=x2−101 = −5+−101 = −1051 substitute to the expression (x−3)(x+5)>0 (−1051−3)(−1051+5)>0
81
--- > 0
100
one of the solutions of our inequality is: x<−5
_____ _____
\ /
-------ο-------ο-------
x2 x1
Other solutions will get with the changeover to the next point etc. The answer: x<−5 x>3